2020
DOI: 10.1590/pboci.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Ultrashort Persian Version of Oral Health Impact Profile (OHIP-5) Questionnaire

Abstract: To validate the ultrashort (5-item) Persian version of OHIP by investigating its psychometric properties. Material and Methods: Construct validity was assessed by examining the correlation between OHIP-5 scores and self-reported oral health status, judgment for dental treatment needs and the number of natural teeth. Reliability was calculated using Cronbach's alpha and corrected item-total correlation. Effect size (ES) and Standardized Response Mean (SRM) were calculated for the responsiveness of the scale and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Comparison of chemical composition of the three mouthwashes used in the present study showed that cetylpyridinium chloride and chlorhexidine mouthwashes are alcohol‐free and essential oils contains alcohol in its structure. The production of non‐alcoholic mouthwashes has been considered by reputable pharmaceutical companies around the world in the recent years because the presence of ethanol causes some mouthwash users to experience a burning sensation, unpleasant taste and dry mouth after consumption 15 . Besides, it has been shown that long‐term use of mouthwashes containing a high percentage of ethanol may predispose the users to development of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of chemical composition of the three mouthwashes used in the present study showed that cetylpyridinium chloride and chlorhexidine mouthwashes are alcohol‐free and essential oils contains alcohol in its structure. The production of non‐alcoholic mouthwashes has been considered by reputable pharmaceutical companies around the world in the recent years because the presence of ethanol causes some mouthwash users to experience a burning sensation, unpleasant taste and dry mouth after consumption 15 . Besides, it has been shown that long‐term use of mouthwashes containing a high percentage of ethanol may predispose the users to development of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The production of non-alcoholic mouthwashes has been considered by reputable pharmaceutical companies around the world in the recent years because the presence of ethanol causes some mouthwash users to experience a burning sensation, unpleasant taste and dry mouth after consumption. 15 Besides, it has been shown that long-term use of mouthwashes containing a high percentage of ethanol may predispose the users to development of oral cancer. Optimum concentration of 50-70% ethanol is required for its antiseptic effects, and this percentage is lower in mouthwashes (26% in Listerine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrashort version of the Oral Health Impact Profile (OHIP-5) was used to measure OHQoL. The Persian version of this tool has been validated by Nazeri et al 12 This scale assesses OHQoL through questions about dental or oral complications based on one’s experience in the previous 12 months. The answers to the questions are scored from 0 to 4 for never, hardly ever, occasionally, often, and always, respectively.…”
Section: Methodsmentioning
confidence: 99%